Determinants That Influence Financial Sustainability Through Profitability - Adhim, Chairul; Mulyati, Mulyati (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to determine whether LDR, NPL, BOPO, and CAR have a direct effect on FSR through ROA in banks listed on the Indonesia Stock Exchange. The sample was selected using purposive sampling with a total sample of 40 banks. The research data was tested using path analysis. The results of the direct analysis show that LDR does not affect FSR, while NPL, BOPO, and CAR have a negative and significant effect on FSR. Additionally, ROA has a positive and significant effect on FSR. Furthermore, LDR and CAR do not affect ROA, whereas NPL has a positive and significant effect, and BOPO has a significant negative effect on ROA. The results of the indirect analysis show that LDR, NPL, and CAR do not affect FSR through ROA, whereas BOPO has a significant negative effect on FSR through ROA.